THE DEVELOPMENT OF THE PORT ACTIVITIES ON THE ROMANIAN SEA COAST OF THE BLACK SEA FROM ANTIQUITY TO MODERN TIMES - Iuliana Mirela Glogoveanu (Romanian Journal of Historical Studies, 2019)
Surveillance of commercial and passenger traffic has been and is currently a national security activity involving the use of a modern infrastructure, which allows the rapid intervention of competent institutions. This has been a necessity from ancient times for the Dobrogea area, and bears the mark of those who came to these lands to carry out transport and trade activities in this area of our country. In this context, Romania has evolved with ups and downs in terms of transportation, navigation and traffic surveillance activities in its maritime and fluvial area.